Oxodealkenylative Cleavage of Alkene C(sp3)−C(sp2) Bonds: A Practical Method for Introducing Carbonyls into Chiral Pool Materials. (2nd December 2019) - Smaligo, Andrew J.; Wu, Jason; Burton, Nikolas R.; Hacker, Allison S.; Shaikh, Aslam C.; Quintana, Jason C.; Wang, Ruoxi; Xie, Changmin; Kwon, Ohyun
Abstract: Reported herein is a one‐pot protocol for the oxodealkenylative introduction of carbonyl functionalities into terpenes and terpene‐derived compounds. This transformation proceeds by Criegee ozonolysis of an alkene, reductive cleavage of the resulting α‐alkoxy hydroperoxide, trapping of the generated alkyl radical with 2, 2, 6, 6‐tetramethylpiperidin‐1‐yl (TEMPO), and subsequent oxidative fragmentation with MMPP. Using readily available starting materials from chiral pool, a variety of carbonyl‐containing products have been accessed rapidly in good yields. Abstract : Ein Ein‐Topf‐Protokoll für die Einführung von Carbonylfunktionalitäten in Terpene erfolgt durch Criegee‐Ozonolyse eines Alkens, reduktive Spaltung der resultierenden α‐Alkoxyhydroperoxide, Abfang des erzeugten Alkylrestes mit TEMPO und oxidative Fragmentierung mit Magnesiumbis(monoperoxyphthalat)hexahydrat. Eine Vielzahl von Carbonylprodukten wurde schnell und mit guten Ausbeuten erhalten.